2013
DOI: 10.2139/ssrn.2253840
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence on Income Comparisons and Subjective Well-Being

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
3
18
2
Order By: Relevance
“…1 One alternative to researcher-defined reference-group income is to exploit instead respondent-supplied measures of reference-group income: Mayraz et al (2009), de la Garza et al (2010, and Goerke and Pannenberg (2013) all use such subjective information on cardinal referencegroup income and conclude that income comparisons do indeed affect reported satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…1 One alternative to researcher-defined reference-group income is to exploit instead respondent-supplied measures of reference-group income: Mayraz et al (2009), de la Garza et al (2010, and Goerke and Pannenberg (2013) all use such subjective information on cardinal referencegroup income and conclude that income comparisons do indeed affect reported satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Another branch of studies relies on direct evidence from survey data. This research for example identified colleagues (Clark and Senik, 2010, with European data), people in your occupation (Goerke and Pannenberg, 2013, with German data) and friends (Yamada and Sato, 2013, with Japanese data) as the most relevant ref-…”
mentioning
confidence: 99%
“…However, some data contain more explicit information on a respondent's "true" reference group. For example, Goerke and Pannenberg (2013) use data from three pretest modules of the SOEP for the years 2008 to 2010, which include information on participants' perceived relative income position and the comparison intensity for nine reference groups (neighbors, friends, colleagues at the workplace, other people in the respondent's occupation, people in the same age, parents when they were in respondent's age, partner, other women, other men). A theoretical approach in which the reference group is endogenous is given by Falk and Knell (2000).…”
Section: Reference Groupsmentioning
confidence: 99%